Perencanaan Drainase Pada Ruas Jalan Desa Loki Sta 00+000 – 02+500 Kabupaten Seram Bagian Barat - Fadhel Alief Muhammad; Rudi Serang; Standy Johannes (Universitas Pahlawan Tuanku Tambusai, 2024)
Drainage is an important component as a complementary building for roads. The drainage system was built to channel water discharge originating from the hydrological cycle and waste water from household and community activities. A well-built drainage system can prevent waterlogging which can disrupt the activities of the surrounding community and can also prevent road damage. This research method was carried out directly at the research location to obtain existing data directly from the field and library research. Based on the planned discharge, the author uses the People's Log Distribution III, to calculate the dimensions of the drainage channel on the Loki village road. From the results of research and drainage planning calculations, it was found that the planned water discharge on the Loki village road was 0.472 m3/second. And from the results of planning the channel dimensions, it was obtained that the width of the top of the channel was 90 cm, the width of the bottom of the channel was 55 cm, and the depth of the channel was 75 cm.